Simulation of Partial Discharge Induced Electromagnetic Wave in Power Transformer - Nhet Ra; Tomohiro Kawashima; Naohiro Hozumi; Yoshinobu Murakami; Umar Khayam; Suwarno Suwarno (EPI International Journal of Engineering, 2018)
This paper describes the numerical simulation of partial discharge (PD) in oil-filled power transformer using FDTD method (Finite Difference Time Domain). We investigated the effects of oil insulation medium and internal structures on the propagation of electromagnetic signal emitted from the partial discharge source. In this study, partial discharge was modeled as the Gaussian Pulse with the width 20ns. To observe the electromagnetic intensity and also the voltage distribution, three sensors were employed. The magnitude, frequency, and attenuation of the EM wave without internal structure and with internal structure were compared. The Results show that the EM wave intensity attenuated while propagating through the winding and oil insulation. And the time arrival of each signal is different due to its distance from the PD source. The first dominance frequency of the simulation without and with winding and core occur in 1 GHz of frequency. However, the frequency spectrum of simulation with winding and core has a resonance frequency in the low region which is 80 MHz of frequency. This is explained as the winding is considered as a loop antenna